The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0034355219847284
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition: Virtual Reality Program for Facial Emotion Recognition—A Trial Program Targeted at Individuals With Schizophrenia

Abstract: People with severe mental illness (SMI), schizophrenia in particular, show considerable functional impairment in emotional recognition and social perception, which negatively affects interpersonal relationships and social functioning. Owing to its ecological validity, virtual reality (VR) has been observed to improve both assessment and training of emotional recognition skills of people with SMI. This article includes two studies: (a) a descriptive study on the Virtual Reality program for Facial Emotion Recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Third, a recent study [41] examined the effects of a virtual reality-based EMP in patients with schizophrenia; the world has been experiencing an unprecedented public health crisis owing to the COVID-19 pandemic, denoting the necessity to develop EMPs that employ various contactless forms of media. This would allow for the administration of such programs without major hinderances related to the social isolation policies imposed across several countries.…”
Section: Limitationsmentioning
confidence: 99%
“…Third, a recent study [41] examined the effects of a virtual reality-based EMP in patients with schizophrenia; the world has been experiencing an unprecedented public health crisis owing to the COVID-19 pandemic, denoting the necessity to develop EMPs that employ various contactless forms of media. This would allow for the administration of such programs without major hinderances related to the social isolation policies imposed across several countries.…”
Section: Limitationsmentioning
confidence: 99%
“…VR-based assessments were found to be feasible and did not increase anxiety or cause negative experiences . Studies found that clinical samples displayed various indicators of social functioning impairments in these social environments, such as reduced eye gaze and greater interpersonal distance as measured by eye or position tracking technology within the HMD (Choi et al, 2010;Geraets et al, 2018;Han et al, 2014;, greater interpersonal sensitivity (McDonnell et al, 2018), increased physical stress responses (Counotte et al, 2016), less accuracy in facial recall (Dietrichkeit et al, 2020), less accuracy in identifying emotions and social cues (Souto et al, 2013;Souto et al, 2020), higher belief inflexibility bias and more attention to threat and more external attributions (Pot-Kolder et al, 2017), and notably, in six studies, increased paranoid ideation, (Freeman et al, 2010;Hesse et al, 2017;Valmaggia et al, 2015;Veling et al, 2016;. One study used VR as an assessment of social functioning over six sessions in the context of testing an antipsychotic treatment and found that antipsychotic medication significantly improved social functioning as assessed by VR .…”
Section: Head-mounted Display Studiesmentioning
confidence: 99%
“…The diversity of theories has been followed by the increased number of areas in which emotion or affect recognition is taken advantage of, including interaction with people and robotics [7][8][9], intelligent vehicles [10,11], psychiatry and psychotherapy [12,13], and many others. Machine learning (ML) can be utilized for patients experiencing alexithymia accompanying other disorders (autism spectrum disorders, somatoform disorders), i.e.…”
Section: Introductionmentioning
confidence: 99%